Is the São Francisco River a geographic barrier to gene flow in trees of Handroanthus ochraceus? - de Abreu Moreira, Patrícia; Fernandes, G. Wilson (Journal of tropical ecology, 2013)
Many landscape features represent geographic barriers to gene flow, and promote genetic discontinuity. Rivers are effective barriers. However, most studies on this subject have focused on animals and only a few have focused on plants. We studied the genetic structure and gene flow of the tropical tree Handroanthus ochraceus (Bignoniaceae) on both banks of the São Francisco River in a Brazilian seasonally dry tropical forest. The São Francisco is located in eastern Brazil and is 600 m wide at the study site. Our hypothesis was that the river is a geographic barrier to gene flow of H. ochraceus trees. We sampled two populations on the left bank and one population on the right bank. We used seven microsatellites to genotype 212 individual plants. All populations had low polymorphism and genetic diversity, but high inbreeding. There was no genetic differentiation among populations and, consequently, the estimated gene flow was high for all pairs of populations. The genetic relatedness among individuals from populations of the same margin did not differ from the relatedness among individuals from populations of opposite margins. Hence, the São Francisco River is not an effective geographic barrier to gene flow among H. ochraceus populations.